2006
DOI: 10.2466/pr0.98.2.427-432
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Self-Efficacy and Organizational Citizenship Behaviors

Abstract: The aim of the study was to investigate the relationship between teachers' instructional efficacy and their organizational citizenship behavior. Questionnaires were sent to a sample of 1,100 French Canadian high school teachers. A response rate of 44.36% was obtained (279 women and 208 men whose mean age was 40.4 yr.) Teachers' instructional efficacy was assessed with a French Canadian version of the Teacher Efficacy Scale and organizational citizenship behavior was assessed with a questionnaire constructed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
2
17
0
5
Order By: Relevance
“…First, Wang et al (2018) demonstrated that when humble leaders appreciate subordinates' strengths, even view themselves as students of their subordinates' strengths (Owens and Hekman, 2012), subordinates' perceptions of self-efficacy and self-worth will be enhanced. Given that self-efficacy has a close relation to OCB (Dussault, 2006;Kao, 2017), humble leadership might have a positive correlation with OCB. Second, the appreciation of subordinates' contributions that humble leaders express can help subordinates recognize the importance of their contributions to organizations and, in turn, facilitates subordinates' perception of meaning in their jobs (Chen et al, 2018).…”
Section: Humble Leadership and Ocbmentioning
confidence: 99%
“…First, Wang et al (2018) demonstrated that when humble leaders appreciate subordinates' strengths, even view themselves as students of their subordinates' strengths (Owens and Hekman, 2012), subordinates' perceptions of self-efficacy and self-worth will be enhanced. Given that self-efficacy has a close relation to OCB (Dussault, 2006;Kao, 2017), humble leadership might have a positive correlation with OCB. Second, the appreciation of subordinates' contributions that humble leaders express can help subordinates recognize the importance of their contributions to organizations and, in turn, facilitates subordinates' perception of meaning in their jobs (Chen et al, 2018).…”
Section: Humble Leadership and Ocbmentioning
confidence: 99%
“…As an outcome variable, Bogler and Somech (2004) reported that OCB was associated with teacher empowerment, specifically as measured by teacher involvement in decision making, status, and self‐efficacy. Dussault (2006) found positive and significant correlations between self‐reported teaching efficacy and various dimensions of OCB, such as altruism, courtesy, conscientiousness, and civic virtue.…”
Section: Ocb In Educational Settingsmentioning
confidence: 99%
“…Another important variable of the study is self-efficacy. Although limited in number, studies reveal that self-efficacy beliefs of individuals are also found to be positively related to their citizenship behaviour (Bogler & Somech, 2004; Dussault, 2006; Somech & Drach-Zahavy, 2000). However, the current study centres on a model which brings together the dimensions of workplace spirituality and self- efficacy of teachers impacting citizenship behaviours directed towards individuals (OCB-I) and towards the institutions (OCB-O).…”
Section: Introductionmentioning
confidence: 99%